The peaceful expansion of the English language in Europe. A tool of integration or a facet of quiet colonization? - Odrowąż-Coates, Anna (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
The paper serves as an invitation to rethink the global growth of English. It refers to the benefits and adverse effects associated with the English language expansion in Europe, in historical, political and cultural contexts. The findings of the paper are framed by the optics of social pedagogy, critical theory and post-colonial thought.
Keywords: colonization; culture; globalization; integration; identity; language